The Soviet Renovationist Schism and the Problem of the Transition to the New Calendar in the 1920s - Priest Alexander V. Mazyrin (Вестник Екатеринбургской духовной семинарии, 2025)
The paper is devoted to the attempts of the God-fighting communist government to impose a Western calendar alien to the Russian Orthodox Church, with the assistance of the Renovationist schism inspired by this government. It shows who and for what purpose initiated this reform (the Anti-Religious Commission under the Central Committee of the Russian Communist Party (of the Bolseviks) to deepen the schism of the Church), and with what enthusiasm the Soviet schismatics themselves joined in this matter, first of all their leader, the false-metropolitan Antonin (Granovsky).The article also shows how in 1923 the transition to the new style began to be carried out by the Renovationists in practice. The external and internal church context of the events is considered: the positions of the Eastern Patriarchs, the Holy Patriarch of Moscow Tikhon (Bellavin), and the Orthodox Russian flock. Presented are various evidences of its sharp rejection of the new calendar style in the liturgical life. In such a situation, the Renovationists had to maneuver: on the one hand, demonstrating their commitment to the ideas of the church revolution and solidarity with the Soviet policies, on the other hand, trying not to completely alienate ordinary believers from themselves, actually allowing the old calendar for church holidays to be preserved locally. After the resignation of Antonin (Granovsky) in the summer of 1923, the leaders of the split advocated the new style more in words than in deeds. The celebration of the Nativity of Christ in December 1924 was especially significant, when almost none of the faithful came to the service in the captured Cathedral of Christ the Saviour, headed by the new schismatic leader, false-metropolitan Evdokim (Meshchersky). Since the summer of 1924, the Renovationists began to link the transition to the new style with the final solution of the Easter Calendar issue at the “Ecumenical Council” initiated by the Patriarchate of Constantinople, which, however, eventually never took place. In 1925, the leadership of the RCP(b) itself abandoned the imposition of the Gregorian style on Orthodox believers, after which the calendar problem virtually disappeared (with a few exceptions: for example, in Soviet Georgia, where its own Renovationists operated).